Studies on anatomy of flower bud differentiation and development in Cattleya - WU Gen-liang; SUN Yao; SHEN Guo-zheng; XI Du-jun (浙江大学学报. 农业与生命科学版)
The paraffin sections were used to observe the process of flower bud differentiation in Cattleya‘Blc- Shinfong Princess’. The results show that the flower bud differentiation process could be divided into six phases: inflorescence primordium differentiation phase, bract primordium differentiation phase, flower primordium differentiation phase, sepal primordiurn differentiation phase, petal primordium differentiation phase, and gynostemium primordium differentiation phase. The order of flower bud differentiation ran from outside to inside. When the vegetative buds reached 12 cm long, the differentiation of flower bud began; when the vegetative buds reached 36 cm long, the differentiation of flower buds was basically completed.